2013
DOI: 10.1016/j.bbadis.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate prevents oxidative phosphorylation deficit and promotes mitochondrial biogenesis in human cells from subjects with Down's syndrome

Abstract: A critical role for mitochondrial dysfunction has been proposed in the pathogenesis of Down's syndrome (DS), a human multifactorial disorder caused by trisomy of chromosome 21, associated with mental retardation and early neurodegeneration. Previous studies from our group demonstrated in DS cells a decreased capacity of the mitochondrial ATP production system and overproduction of reactive oxygen species (ROS) in mitochondria. In this study we have tested the potential of epigallocatechin-3-gallate (EGCG) - a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 54 publications
3
98
0
Order By: Relevance
“…For instance, isoflavones (genistein, daidzein, and formononetin) in rabbit renal proximal tubular cells (Rasbach and Schnellmann, 2008), flavones (baicalein, its 7-O-glucuronide baicalin, and wogonin) in L6 skeletal muscle cells (Im et al, 2012), and flavan-3-ol epigallocatechin-3-gallate in skin fibroblasts from Down's syndrome patients (Valenti et al, 2013) all activate the SIRT1/ PGC-1a pathway. In contrast to the SIRT1-inducing effect of genistein (Rasbach and Schnellmann, 2008), this isoflavone also reduces SIRT1 mRNA and protein expression and induces SIRT1 nuclear exclusion into the cytosol of the human prostate cancer cell lines LNCaP and PC-3 (Kikuno et al, 2008).…”
Section: Polyphenols and Other Natural Productsmentioning
confidence: 99%
“…For instance, isoflavones (genistein, daidzein, and formononetin) in rabbit renal proximal tubular cells (Rasbach and Schnellmann, 2008), flavones (baicalein, its 7-O-glucuronide baicalin, and wogonin) in L6 skeletal muscle cells (Im et al, 2012), and flavan-3-ol epigallocatechin-3-gallate in skin fibroblasts from Down's syndrome patients (Valenti et al, 2013) all activate the SIRT1/ PGC-1a pathway. In contrast to the SIRT1-inducing effect of genistein (Rasbach and Schnellmann, 2008), this isoflavone also reduces SIRT1 mRNA and protein expression and induces SIRT1 nuclear exclusion into the cytosol of the human prostate cancer cell lines LNCaP and PC-3 (Kikuno et al, 2008).…”
Section: Polyphenols and Other Natural Productsmentioning
confidence: 99%
“…Although EGCG shows a cytoprotective effect at low concentrations (10-20 µM) (37), it has been reported that consumption of green tea-derived supplements at a high dose (120 mg/kg) can produce toxic effects in rodents (38).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function is notably impaired in DS, 21 which may contribute to several DS-linked developmental abnormalities. In lymphoblast and fibroblast cultures from DS subjects treatment with EGCG (20 mM) has been shown to rescue mitochondrial function and promote mitochondrial biogenesis.…”
Section: Effects Of Egcg In Individuals With Down Syndromementioning
confidence: 99%
“…In lymphoblast and fibroblast cultures from DS subjects treatment with EGCG (20 mM) has been shown to rescue mitochondrial function and promote mitochondrial biogenesis. 21 This study prompted research aimed at establishing whether a similar effect was replicated in vivo. 22 A child (10-year and 3-monh-old) with DS was treated with ECCG (10 mg/kg/day) plus fish oil daily for six months.…”
Section: Effects Of Egcg In Individuals With Down Syndromementioning
confidence: 99%